Mengupas Kritik Sosial pada Kumpulan Puisi Mbeling Karya Remy Shylado melalui Rima, Tipografi, dan Enjambemen - Salwa Pramesti Maharani; Munaris; Mulyanto Widodo; Edi Suyanto; Siti Samhati (ESTETIK : Jurnal Bahasa Indonesia, 2025)
Research on social criticism in the collection of Puisi Mbeling by Remy Sylado is important because these aspects emerged as a response to the repression of the Orde Baru through the use of rhymes, spontaneous line breaks, and typography that deviates from conventions to become a symbol of rebellion against the oppressive social and political system. This study aims to examine social criticism in the collection of Puisi Mbeling by Remy Shylado through rhyme, typography, and enjambment. Qualitative methods were used in this study on 5 data sources on poetry that best represent social criticism, such as 1) Dendam pada Imperialisme-Kolonialisme, 2) Cintaku Tati, 3) Pelestarian Tradisi Birokrasi, 4) Atas Nama Rakyat, and 5) Catatan Kaki. These poems are included in the book Puisi Mbeling by Remy Shylado published by Kepustakaan Populer Gramedia in 2023 (second printing). The data collection and analysis techniques were carried out in several ways, namely 1) reading carefully, 2) collecting by marking data, and 3) presenting the results of data analysis in each line and stanza of the poem. The results of the study showed that the poet succeeded in peeling away social criticism in the collection of Puisi Mbeling through analysis of rhyme, typography, and enjambment in a brilliant and interesting way.